Comparison of Intravenous Lipid Emulsion, Bicarbonate, and Tailored Liposomes in Rabbit Clomipramine Toxicity. (15th October 2013) - Cave, Grant; Harvey, Martyn; Shaw, Tom; Damitz, Robert; Chauhan, Anuj; Schneider, Sandra
Abstract Objectives Liposome (LIP)‐like lipid dispersions have emerged as useful detoxification vehicles in vitro. The authors compare resuscitation with tailored LIPs, 20% intravenous lipid emulsion (ILE), and sodium bicarbonate (BIC), in a rabbit model of clomipramine toxicity. Methods Sedated, instrumented New Zealand white rabbits underwent clomipramine infusion at 3.2 mg/kg/min to 50% baseline mean arterial pressure (MAP) and then at 1.6 mg/kg/min for 30 minutes. BIC (3 mL/kg 8.4%), ILE (3 mL/kg 20%), or LIP (24 mg/kg) were infused as rescue treatments at toxicity and were repeated at 10 minutes (n = 5 in each group). Results Thirty‐minute MAP was greatest in ILE‐treated animals: 61 mm Hg ILE (interquartile range [IQR] = 49 to 64 mm Hg), 43 mm Hg LIP (IQR = 36.5 to 49 mm Hg), and 10 mm Hg BIC (IQR = 10 to 44 mm Hg; all p = 0.02). Two of the five BIC‐treated animals survived to 30 minutes, compared with all five of the ILE‐treated animals and all five of the LIP‐treated animals (p = 0.044). Conclusions Both ILE and LIPs improved hemodynamic recovery compared with bicarbonate in clomipramine‐induced cardiotoxicity in rabbits. Greater 30‐minute MAP was observed in the ILE group.